Can We Observe the Gravitational Quantum States of Positronium?. (8th March 2015) - Crivelli, P.; Nesvizhevsky, V. V.; Voronin, A. Yu.
Abstract : We consider the feasibility of observing the gravitational quantum states of positronium. The proposed scheme employs the flow-throw technique used for the first observation of this effect with neutrons. Collimation and Stark deceleration of Rydberg positronium atoms allow selecting the required velocity class. If this experiment could be realized with positronium, it would lead to a determination ofg for this matter-antimatter system at the few % level. As discussed in this contribution, most of the required techniques are currently available but important milestones have to be demonstrated experimentally before such an experiment could become reality. Those are the efficient focusing of a bunched positron beam, Stark deceleration of Rydberg positronium, and its subsequent excitation into states with large angular momentum. We provide an estimate of the efficiencies we expect for these steps and assuming those could be confirmed we calculate the signal rate.